Fundamental natural frequencies investigation for a typical 5-MW wind turbine blade. (April 2020) - Alsabagh, Abdel Salam Y; Fayyad, Sayel M; Darweesh, Nihad; Alfaqs, Fadi
Continuous structures such as beams, rods and plates can be modelled by discrete mass and stiffness parameters and analysed as multi-degree-of-freedom systems. The analysis of structural vibration is necessary to obtain the natural frequencies of a structure and the response to the external excitation. In this way, it can be determined whether a particular structure will fulfil its intended function and, in addition, the results of the dynamic loadings acting on a structure can be predicted. The lack of a sober analytical research about the vibrational behaviour of the 5-MW wind turbine blade pushed us to investigate about this crucial issue, however, most of the discreet researches are concerned with the aerodynamic effects rather than structural analysis. In this article, Rayleigh–Ritz method was implemented for a typical 5-MW wind turbine blade. MATLAB codes were developed and natural frequencies were obtained for both flapwise and edgewise vibrational behaviour. A good agreement was observed between the analytical results and the manufacturer results.